Wide DC Output Voltage Range Buck-Boost 6-Module Y-Rectifier Featuring Full Power Delivery in 3-Phase and 1-Phase Operation - David Menzi; Lorenz Kappeler; Patrick Ziegler; Davide Biadene; Johann W. Kolar (IEEE Access)
Power factor correction rectifiers/inverters with wide input-output voltage ranges are instrumental in applications with widely varying dc voltages such as photovoltaic inverters. Aiming at compatibility with various grid infrastructures, the rectifiers should further feature nominal-power operation in both, a single-phase and a 3-phase grid. The recently proposed 6-Module (6M) Y-rectifier advantageously features quasi-single-stage buck-boost capability and nominal-power single-phase operation with reduced component over-dimensioning compared to state-of-the-art topologies. Thus far, the 6M Y-rectifier was analyzed based on theoretical considerations only and this paper provides experimental evidence of the full functionality of the concept. A detailed analysis of the main power component stresses and high-frequency noise emissions is conducted for a 6M Y-rectifier covering a wide dc output voltage range of 200V to 750V and operating in a 400V 3-phase and a 240V split-single-phase grid. This study allows to identify suitable power component realizations for an 11kW hardware demonstrator featuring a volumetric power density of 9.4kW/dm3 (154W/in3) and a peak efficiency of 98.6%. All relevant aspects, that is, prototype system startup, transient and steady-state buck-boost operation, conversion efficiency, as well as compliance with the CISPR11/ClassA emission limits in both a 3-phase and a single-phase grid, are verified experimentally.